PENGARUH EVALUASI KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN LEBAK - Rina Dwi Utami; Karunia Julian (Universitas La Tansa Mashiro, 2017)
The financial performance area needed to measure the ability of an area in managing their finances its territory. The purpose of this research isto find out the financial performance of local government by using some financial ratios,are among themis the ratio of degree of decentralization, the dependency ratio, the ratio of independence, the ratio of the effectiveness and efficiency, growth ratio.This research was conducted the office of BAPENDA and the data used in quantitative data that is the realization of the report budget (LRA) and Target. The method is done in this study is to use quantitative descriptive methods to measure the financial performance.Results of the study showed that the ratioof degrees decentralization belongs to low or less because it is at intervals <20% with the average ratio of 12%. Result the ratio of the dependency rate belongs to very high views of the average dependency rate of 67% that is to be at intervals area >50%, the ratio of low belongs to the independence once with an average ratio of 18%. The result of the average ratio of effectiveness of 102% because it is on intervals >100% who belongs into the criteria very effective and the ratio of efficiency get result into an average of 97% can be categorized into efficient criteria. The original income growth ratio of the area, the revenue growth, operating expenses growth, capital expenses growth entirely showed a positive growth.